Goal structures in family firms: empirical evidence on the relationship between firm and family goals - Ann-Kristin Achleitner; Reiner Braun; Stephanie Schraml; Juliane Welter (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
Goal structures in family firms seems of particular interest to the field as the overall orientation and the objectives of family firms are determined in an area of potential conflict between the two subsystems of firm and family. We asked shareholders of German family firms to rate the importance of certain goals in the organization's management. By doing a principal component analysis on the ratings given, we identified four central categories of goals that permit a much more detailed analysis than would a simple differentiation between family-related and firm-related goals. The differences among organizations in the identified dimensions of short-term and long-term family goals, as well as growth- and value-orientated firm goals are then assessed in more detail. Among other aspects, we found the existence of an advisory board to be the strongest driver of goal preferences along these dimensions. Theoretically, our findings indicate that, depending on family firm characteristics, agency and stewardship theory are both useful in explaining the goals of the relevant systems of family and firm.
Keywords: L21; L26; 330; family firms; goal preferences; agency theory; stewardship theory; Familienunternehmen; Betriebswirtschaftliches Ziel; Familie; Eigeninteresse; Präferenztheorie; Prinzipal-Agent-Theorie